Self-assembled conjugated polyelectrolyte–surfactant complexes as efficient cathode interlayer materials for bulk heterojunction organic solar cells. Issue 47 (5th November 2015) - Chevrier, Michèle; Houston, Judith E.; Kesters, Jurgen; Van den Brande, Niko; Terry, Ann E.; Richeter, Sébastien; Mehdi, Ahmad; Coulembier, Olivier; Dubois, Philippe; Lazzaroni, Roberto; Van Mele, Bruno; Maes, Wouter; et al.
Abstract : Conjugated polyelectrolyte–surfactant cathodic interface layers lead to improved power conversion efficiencies in organic solar cells. Abstract : Interfacial engineering is poised to play a key role in delivering solution-processable organic solar cells that simultaneously feature low cost and high efficiency. Here, we report the strategic design, synthesis and characterisation of phosphonium-functionalised polythiophene homo- (P3HTPMe3 ) and diblock (P3HT- b -P3HTPMe3 ) conjugated polyelectrolytes (CPEs) coupled with either bromide (Br − ) or dodecylsulfate (DS − ) surfactant counterions, for application as cathodic interlayers in polymer solar cells. The counterion is shown to have a pronounced effect on the properties of the CPEs in solution. Optical studies revealed that the bulkier DS − counterion hinders interchain interactions more effectively, leading to a moderate blue-shift in the absorption and emission maxima. Similarly, small-angle neutron scattering (SANS) studies also indicated that the solution structures, solvent content, and therefore hydrophobicity, were extremely dependent on both the CPE structure and counterion. The effect of the CPE structure on the thermal properties of the CPE–surfactant complexes was also investigated by Rapid Heat–Cool calorimetry (RHC) measurements. CPE–DS complexes were subsequently employed as cathodic interfacial layers and shown to boost the efficiency of PBDTTPD : PC71 BM solar cells, leading to enhanced power conversion efficiencies of 8.65% and 8.78% (on average) forP3HTPMe3, DS andP3HT- b -P3HTPMe3, DS, respectively. These values are significantly higher (∼20%) than those for the corresponding device incorporating a Ca interfacial layer (7.18%), which is attributed to an increase in short-circuit current density. Atomic force microscopy studies revealed distinctions in the adhesion efficiencies of the CPE–DS complexes to the photoactive layer, which is attributed to differences in the relative hydrophobicity of the CPEs in the deposition solution.